Openness to experience as a cognitive competence - Szyszko, Monika (Studia Psychologica: Theoria et praxis, 2007)
In agreement with Carl Rogers’s theory, openness to experience is conceptualized as a cognitive competence, which consists of; 1. openness to own feeling, emotions and needs; 2. openness to life novelty, new ideas and other people. Being more open means being more able to perceive and interpret surrounding environment in a creative and comprehensive way. In effect an open individual can better adapt to life, is more congruent and can build such relationship with others that are free of stereotypes. 35 - Items Inventory (OND35) was developed to measure the level of openness to experience. The experimental data indicate that individuals who are open to experience perceive new situation as a challenge and strive for better understanding of themselves. Other data suggest, that openness correlates positively with toleration of ambiguity, emotional intelligence, satisfaction from interpersonal relationships and can be improved through therapy. It can be assumed that openness to experience facilitates effective coping with difficult life problems and is important in building a stable identity.